Learning practice in mathematics education department of Universitas Muhammadiyah Surabaya during covid-19 pandemic - Iis Holisin; Himmatul Mursyidah (PROCEEDING UMSURABAYA, 2020)
Abstract. The purpose of this research is to describe the practice of learning during thecovid-19 pandemic in Mathematics Educations Department at Teacher Training andEducation Faculty of Universitas Muhammadiyah Surabaya (UM Surabaya). The research used descriptive explorative methods with qualitative approach. The research subjects consisted of students and lecturers in the mathematics education department at Teacher Training and Education Faculty of UM Surabaya. Data collected by documentation, questionnaire, and interview techniques. Triangulation of sources was used to test data validity. Data from students were compared by lecturers‘ data. The data were analysed through three stages, i.e., reduction, data presentation, and drawing conclusions. The results showed that during the covid-19 pandemic, there are four alternatives learning practices implemented by lecturers. Each alternative consist of 3 stages: delivery, activity, and assessment. The online media used were Zoom, WhatsApp, YouTube, e-mail and Google Meet. The most effective online learning media according to lecturers is Zoom. Meanwhile, according to students, the most effective online media is YouTube. The obstacles faced by students and lecturers are internet network and quota. The learning practices carried out by lecturers during the covid-19 pandemic helped students to keep learning